Pharmacoepidemiological Evaluation of Glaucoma among Patients Attending Ophthalmology Outpatient Department: A Hospital-based Cross-sectional Study - Rashmi Ranjan Bhadra; Jayanti Prava Behera; Aurobindo Samantray; Padmaja Priyadarshini Kar; Y Roja Ramani (Journal of Clinical and Diagnostic Research)
Introduction: Glaucoma is the leading cause of irreversible blindness in India, accounting for 5.5% of total blindness. In South Odisha, there are limited studies evaluating the pharmacoepidemiology of glaucoma. Understanding the sociodemographic characteristics of glaucoma patients, along with their medication usage and prescribing trends, is essential for optimising disease management at tertiary care centers. Aim: To evaluate the sociodemographic characteristics of glaucoma patients and the drug utilisation pattern of anti-glaucoma medications in the study population. Materials and Methods: The present hospital-based observational cross-sectional study was performed from September to October 2023. Based on previous literature and the prevalence of glaucoma, the sample size was estimated to be 70. A standardised case record form was used for data collection, which included the patients’ demographic details and the drugs prescribed. Data were analysed using MS Excel and IBM Statistical Package for Social Sciences (SPSS) Version 25 software. Fisher’s Exact test was employed to establish an association between age groups (<50 years and ≥50 years) and gender association with combination therapy and monotherapy. The Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) systems as per World Health Organisation (WHO) and WHO core prescribing indicators were used as study tools for pharmacoepidemiological evaluation. Results: A total of 70 patients participated in the present study in which female preponderance was observed. The most common age group was 50-70 years. Patients were mostly affected by open angle glaucoma 48 (68.57%) compared to angle closure glaucoma 22 (31.43%). A total of 114 drugs were prescribed for the treatment of glaucoma, with an average of 1.63 drugs per prescription. Combination therapy was prescribed for 41 (58.57%) of patients, with the most commonly used combination being brimonidine and timolol 30 (73.17%), followed by dorzolamide and timolol 11 (26.83%). Monotherapy was used for 29 (41.43%) of patients, where dorzolamide 16 (55.18%) was the drug most frequently prescribed, followed by timolol 8 (27.58%) and Latanoprost 5 (17.24%). No statistically significant association was found between gender distribution and the two age groups (<50 years and ≥50 years) with combination therapy or monotherapy. Conclusion: This study provided a detailed analysis of the sociodemographic characteristics of glaucoma patients and evaluated the utilisation pattern of anti-glaucoma drugs. By focusing on rational drug use, this research aimed to improve the understanding of prescribing trends and identify areas for optimising treatment practices in glaucoma management.